Exploring the Path from Social Media and Entrepreneurship Education to Entrepreneurial Interest: The Intervening Effect of Entrepreneurial Mentality - Ummul Khaerani; Novia Fitri Ramadani; Andika Isma; Wiwin Riski Windarsari; Betania Kartika Muflih (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2025)
This study explores the influence of social media and entrepreneurship education on students’ entrepreneurial interest at Makassar State University, with entrepreneurial mentality serving as a mediating variable. In the context of Indonesia’s economic development—where the number of entrepreneurs plays a critical role—the relevance of entrepreneurship education at the university level becomes increasingly important. A quantitative research approach was adopted using a survey method, involving 139 student respondents. Data were collected through a structured questionnaire measuring four key variables: entrepreneurship education, social media usage, entrepreneurial mentality, and entrepreneurial interest. The analysis results indicate that both entrepreneurship education and social media have a significant and positive impact on students’ entrepreneurial interest. Moreover, entrepreneurial mentality functions as an effective mediator, strengthening the relationship between independent variables and entrepreneurial interest. These findings offer valuable insights for enhancing entrepreneurship curricula in higher education and utilizing social media as a strategic tool to foster entrepreneurial aspirations among students. This research contributes to academic discourse and offers practical implications for educators and policymakers seeking to cultivate entrepreneurial potential in the younger generation.